Genetic variability, correlation and path analysis in fastigiata and hypogaea sub-species of groundnut (Arachis hypogaea L.): GENETIC VARIABILITY, CORRELATION AND PATH ANALYSIS IN SUB-SPECIES OF GROUNDNUT - SIMA SINHA; M H RAHMAN; CHANDAN KISHORE (Journal of Oilseeds Research, 2019)
The investigations on the genotypic and phenotypic variability, correlations and path coefficient analysis were conducted for nine characters in twenty genotypes each for two sub species of groundnut namely fastigiata (Spanish/Valencia) and hypogaea (Virginia). Analysis of variance revealed significant differences among the genotypes for all characters except per cent ofsound mature kernel in fastigiata (Spanish) group. The magnitude of phenotypic coefficient of variance (PCV) and genotypic coefficient of variance (GCV) was larger for number of primary branches and 100 kernel weights in hypogaea than fastigiata sub-species. Number of pods per plant in hypogaea showed greater heritability than fastigiata. Genetic advance as per cent of mean for number of pods per plant, 100 kernel weight and pod yield per plant displayed better estimates in hypogaea whereas length of primary branches, height of main axis and 100 kernel weight were higher in fastigiata sub-species. Number of pods per plant was highly significant and positive with pod yield per plant in both sub-species while number of primary branches and percentage of oil was positive and highly significant only in case of hypogaea sub-species. Path coefficient analysis exhibited that the length of primary branches, number of pods per plant, 100-kernel weight and percentage of oil were important for yield improvement in both sub-species of groundnut.